A Study on Performance Appraisal Practices in Indian Public Sector Banks - Mangaleswaran, T.; Srinivasan, P.T. (ABAC School of Management Assumption University, Bangkok, 2007)
The present study was designed to examine the performance appraisal practices of the Public Sector Banks in India. For this purpose three public sector banks were selected, and 449 staff, who attended the training programme, responded to the questionnaire. Data were analyzed employing descriptive statistics and ANOVA. Results reveal that employees of public sector banks show differences in their understanding of performance appraisal evaluation, the regularity and systematic nature of performance appraisal undertaken in their banks. However, on most other aspects pertaining to performance appraisal there were no differences between the public sector banks in India.